Growth and yield of basil (Ocimum sanctum L.) supplemented with liquid organic fertilizer from moringa leaves and chicken eggshells - Andriani Eko Prihatiningrum; Muhammad Abror; Nabila Nurma Riski (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2025)
This study examined the effects of liquid organic fertilizer (LOF) derived from Moringa leaves and chicken eggshell fertilizer on basil (Ocimum sanctum L.) growth and yield. The experiment was conducted at Muhammadiyah University of Sidoarjo and arranged in a randomized block design with three replicates. The research incorporated two factors namely moringa leaf LOF at concentrations of 25, 50, and 75 mL L-1 and chicken eggshell powder at levels of 3, 6, and 9 g. The observation included plant height, leaf number, branches, root length, and fresh and dry weights. Data were analyzed using ANOVA, followed by Tukey’s Honestly Significant Difference (HSD) test at a 5% significance level. Results revealed a significant interaction between LOF and eggshell treatments. The 25 mL L-1 LOF plus 3 g of eggshell fertilizer produced the best results in all growth parameters. This suggests that these organic fertilizers can effectively enhance basil growth. The findings emphasize the potential of combining organic fertilizers at certain levels to optimize basil growth and yield. Keywords: basil growth; moringa extract; organic fertilizer